Plasmon resonance of gold and silver nanoparticle arrays in the Kretschmann (attenuated total reflectance) vs. direct incidence configuration - Rituraj Borah; Rajeshreddy Ninakanti; Sara Bals; Sammy W. Verbruggen (Scientific Reports, 2022)
Abstract While the behaviour of plasmonic solid thin films in the Kretschmann (also known as Attenuated Total Reflection, ATR) configuration is well-understood, the use of discrete nanoparticle arrays in this optical configuration is not thoroughly explored. It is important to do so, since close packed plasmonic nanoparticle arrays exhibit exceptionally strong light-matter interactions by plasmonic coupling. The present work elucidates the optical properties of plasmonic Au and Ag nanoparticle arrays in both the direct normal incidence and Kretschmann configuration by numerical models, that are validated experimentally. First, hexagonal close packed Au and Ag nanoparticle films/arrays are obtained by air–liquid interfacial assembly. The numerical models for the rigorous solution of the Maxwell’s equations are validated using experimental optical spectra of these films before systematically investigating various parameters. The individual far-field/near-field optical properties, as well as the plasmon relaxation mechanism of the nanoparticles, vary strongly as the packing density of the array increases. In the Kretschmann configuration, the evanescent fields arising from p- and s-polarized (or TM and TE polarized) incidence have different directional components. The local evanescent field intensity and direction depends on the polarization, angle of incidence and the wavelength of incidence. These factors in the Kretschmann configuration give rise to interesting far-field as well as near-field optical properties. Overall, it is shown that plasmonic nanoparticle arrays in the Kretschmann configuration facilitate strong broadband absorptance without transmission losses, and strong near-field enhancement. The results reported herein elucidate the optical properties of self-assembled nanoparticle films, pinpointing the ideal conditions under which the normal and the Kretschmann configuration can be exploited in multiple light-driven applications.